Spurring Student Activity Through Action Game-Based Learning (GBL) Method in Sociology Learning - Isroatul Khusna, Nur; Anjani, Sevina Yushinta (IAIN Madura, 2025)
Sociology learning has a fairly broad material, so it requires the accuracy of the use of learning methods to attract student activity. This research was conducted to determine the planning, implementation and evaluation of sociology learning with game learning methods. The method used is qualitative descriptive. Based on the results of the study, learning planning is carried out by applying nine of the ten stages of learning planning according to Dick and Carey's theory which include: identifying general goals, learning analysis, identifying input behaviors and student characteristics, compiling performance goals, choosing learning strategies, developing and selecting learning materials, preparing formative evaluation designs, revising teaching materials and prepare for summative evaluation. The stage that has not been implemented is to prepare a benchmark reference test. The implementation of learning is carried out by applying four of the five theories of the implementation stage, which include: preparation of game selection sessions according to the topic, explanation of concepts according to the learning topic to be delivered, game sessions, and evaluation of the session. The stage that has not been implemented is to summarise the material. Learning evaluation is carried out by implementing all theories of the evaluation stage, including: determining objectives, determining evaluation design, verifying data, processing and analysing data, providing interpretation and conclusions, and follow-up evaluation results.